Implementasi Uji Geolistrik Dan Uji Geoteknik Dalam Penentuan Nilai Faktor Keamanan Daerah Rawan Longsor di Desa Kemiri Kabupaten Jember - Indra Nurtjahjaningtyas (Jurnal Aplikasi Teknik Sipil, 2023)
Landslides are natural disasters that often occur in Indonesia. Landslides have occurred in Kemiri Village, Jember Regency. Kemiri Village is a densely populated area and there is a bustling agro-tourism area. This study aims to analyze the level of vulnerability to landslides using geoelectric tests and geotechnical tests. Geoelectric test is carried out to determine the lithological conditions at the site, geotechnical testing to obtain soil parameters as a determinant of the safety factor value of the research location. The results obtained from the geoelectric test showed a range of resistivity values between 0.72 to 267 and were types of silt to sandstone soils. The factor of safety obtained is between 1.042 - 1.862 which means the value of the factor of safety is relatively low. The value of this factor of safety indicates that in the research location there are still frequent land shifts which are feared landslides will occur.